2021
DOI: 10.1017/s1041610221000399
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal association between loneliness and depressive symptoms in the elderly: a systematic review

Abstract: Objective: Loneliness and the onset of depression in old age are growing problems related to the greater life expectancy nowadays. This review investigated the longitudinal association between loneliness and depressive symptoms in the elderly. Design: A comprehensive search was conducted using three databases (Scopus, PsycInfo, and PubMed) combing for empirical studies published up until July 2020. A total of 4.549 abstracts and 221 full-text articles were assessed. Three authors indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 65 publications
2
43
0
1
Order By: Relevance
“…The second part of the survey consisted of four validated questionnaires on health-related quality of life, loneliness, spirituality, and anxiety/depression. The scores obtained with these four measures were all related to each other in the expected direction [ 93 , 94 , 95 , 96 , 97 ]: for example, health-related quality of life and spirituality were positively associated to each other, and so were loneliness and anxiety/depression scores; moreover, the first pair of variables was negatively associated to the second pair of variables. Furthermore, the data obtained in these questionnaires revealed that the scores obtained by our sample of Italian elderly during the third wave of the COVID-19 pandemic in 2021 were generally in line with those obtained on elderly samples before the pandemic [ 83 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second part of the survey consisted of four validated questionnaires on health-related quality of life, loneliness, spirituality, and anxiety/depression. The scores obtained with these four measures were all related to each other in the expected direction [ 93 , 94 , 95 , 96 , 97 ]: for example, health-related quality of life and spirituality were positively associated to each other, and so were loneliness and anxiety/depression scores; moreover, the first pair of variables was negatively associated to the second pair of variables. Furthermore, the data obtained in these questionnaires revealed that the scores obtained by our sample of Italian elderly during the third wave of the COVID-19 pandemic in 2021 were generally in line with those obtained on elderly samples before the pandemic [ 83 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness is associated with low well-being, poor physical and mental health, and mortality (e.g. Rico-Uribe et al 2018 ; Solmi et al 2020 ; Van As et al 2021 ). Although an individual experience, societal perspectives can contribute to the understanding of loneliness (de Jong Gierveld and Tesch-Römer 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…37 Longitudinal research has found a significant and positive association between loneliness and depressive symptoms. 38 However, personal resources, gender, health status, and age can affect older people's experiences and feelings of loneliness. 25 Participating women were in a worse mood and quality of life and more emotional loneliness than men.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence demonstrating that living alone, especially in the presence of external coercion (such as children leaving home and losing a spouse in old age), can lead to anxiety, depression, and an increased sense of loneliness 37 . Longitudinal research has found a significant and positive association between loneliness and depressive symptoms 38 . However, personal resources, gender, health status, and age can affect older people's experiences and feelings of loneliness 25 …”
Section: Discussionmentioning
confidence: 99%